Pengaruh Pemanfaatan Teknologi Informasi terhadap Kinerja Pegawai dengan Keterbatasan Sumber Daya Manusia di Badan Pertanahan Nasional (BPN) Kabupaten Bekasi Tahun 2023 - Muhammad Avila Putra Herdian; Lusia Astrika (Journal of Politic and Government Studies, 2026)
This research is motivated by the importance of utilizing information technology in improving employee performance amidst limited human resources in government agencies. The purpose of this study is to analyze the effect of information technology utilization on employee performance with limited human resources as a moderating variable at the National Land Agency (BPN) of Bekasi Regency. The study used a quantitative approach with a survey method, a non random sampling technique for 60 respondents, and data collection through a Likert scale questionnaire that has been tested for validity and reliability. Data analysis was carried out using multiple linear regression with the help of SPSS 25. The results showed that the utilization of information technology has a positive and significant effect on employee performance, and a negative effect on limited human resources, which means that the more optimal the use of technology, the more limited human resources can be minimized. In addition, employee performance also has a significant effect on limited human resources. The coefficient of determination value shows a fairly strong contribution from the research variables. In conclusion, the integration of information technology and improving employee performance are key factors in overcoming limited human resources, so it is recommended that continuous training and strengthening of technological infrastructure.